Qualitative research : a guide to design and implementation - Merriam, Sharan B. (John Wiley & Sons, 2016)
"This thoroughly revised and updated classic once again presents aguide to understanding, designing and conducting a qualitativeresearch study. The fourth edition retains the reader-friendly, jargon-free style, making the book accessible to both novice and experiencedresearchers. While the book is practical guide to design andimplementation of a qualitative research study, it also helpsreaders understand the theoretical and philosophical underpinningsof this research paradigm. Drawing on the latest literature as well as both authors'experience with conducting and teaching qualitative research, thefourth edition includes new material on case study research andaction research; discussion of online data sources (video, email, skype); updated discussion of data analysis software packages anduses; new discussion of data analysis strategies, includingnarrative analysis and poetic analysis; and a section on multipleways of presenting qualitative research findings. References, examples, and quotes have all been updated throughout the book"- Resumé vydavatele
Keywords: kvalitativní výzkum; případové studie; qualitative research; case studies; příručky; elektronické knihy; electronic books; handbooks, manuals, etc